Hearing loss prevalence and risk factors among older adults in China. (4th May 2018) - Gong, Rui; Hu, Xiangyang; Gong, Chen; Long, Mo; Han, Rui; Zhou, Lijun; Wang, Fang; Zheng, Xiaoying
Abstract: Objective : This study aims to investigate the prevalence of hearing loss, and to analyse the major demographics and risk factors that influence the prevalence in older adults of China. Design : Cross-sectional investigation. Study sample : Probability proportionate to size sampling (PPS) was adopted for this survey. Among 45, 052 individuals, 6984 older adults (≥60 years) were selected as subjects for this study. Results : The prevalence of hearing loss defined as a speech frequency pure tone average of more than 25 dB HL in the better ear was 58.85%. Age and gender were the factors most strongly associated with hearing loss after multivariate adjustment. Ear disease, diabetes, hypertension, atherosclerosis, noise exposure, and ototoxic drugs were significantly correlated with hearing loss. The largest effects were found for ear disease and noise exposure (OR = 2.83 [95% CI: 2.43–3.29]; OR = 2.59 [95% CI: 1.80–3.72]). Conclusions : Hearing loss is prevalent in nearly two thirds of adults aged 60 years and older in China population. Chronic diseases, ear disease, and noise are important factors in adults aged 60 years and older.